Disciplining Brothers in the Seventeenth-Century Jesuit Province of Aragon - Manning, Patricia W. (Renaissance and Reformation / Renaissance et Réforme, 2014)
This article studies the leave-taking process in the Society of Jesus’ Province of Aragon. According to the Constitutions of the Society of Jesus and decrees of General Congregation 7, the community could decide to dismiss a Jesuit or an individual could request to depart. Provincial and Roman authorities consulted about leave-takings. Although Ignatius of Loyola favoured immediate dismissal of misbehaving men, by the seventeenth century the process had evolved. As archival references demonstrate, the religious community developed atonement processes, including confinement, for wayward Jesuits in the hopes of reforming poor comportment.